A defence of a new perspective on euthanasia. Issue 2 (20th January 2011) - Shaw, David
Abstract : In two recent papers, Hugh McLachlan, Jacob Busch and Raffaele Rodogno have criticised my new perspective on euthanasia. Each paper analyses my argument and suggests two flaws. McLachlan identifies what he sees as important points regarding the justification of legal distinctions in the absence of corresponding moral differences and the professional role of the doctor. Busch and Rodogno target my criterion of brain life, arguing that it is a necessary but not sufficient condition and that it is not generalisable. In this paper I indicate flaws in all of these criticisms, and again suggest that my perspective does add something new to the debate.